2016
DOI: 10.1371/journal.pone.0146143
|View full text |Cite
|
Sign up to set email alerts
|

siMS Score: Simple Method for Quantifying Metabolic Syndrome

Abstract: ObjectiveTo evaluate siMS score and siMS risk score, novel continuous metabolic syndrome scores as methods for quantification of metabolic status and risk.Materials and MethodsDeveloped siMS score was calculated using formula: siMS score = 2*Waist/Height + Gly/5.6 + Tg/1.7 + TAsystolic/130—HDL/1.02 or 1.28 (for male or female subjects, respectively). siMS risk score was calculated using formula: siMS risk score = siMS score * age/45 or 50 (for male or female subjects, respectively) * family history of cardio/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
99
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 31 publications
0
99
0
2
Order By: Relevance
“…Consequently, a formal meta-analysis was precluded due to the heterogeneity of data particularly regarding the diverse demographics of the studied participants and different components of the scores. Surprisingly, the observed incidence/prevalence of MetS at the end of the study is not reported in nearly a third (twenty-nine per cent) of the studies [24,28,31,37,41,42]. For those that reported it, the prevalence/ incidence of MetS ranged from as little as one per cent to as high as thirty-seven per cent (median is thirteen per cent).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…Consequently, a formal meta-analysis was precluded due to the heterogeneity of data particularly regarding the diverse demographics of the studied participants and different components of the scores. Surprisingly, the observed incidence/prevalence of MetS at the end of the study is not reported in nearly a third (twenty-nine per cent) of the studies [24,28,31,37,41,42]. For those that reported it, the prevalence/ incidence of MetS ranged from as little as one per cent to as high as thirty-seven per cent (median is thirteen per cent).…”
Section: Resultsmentioning
confidence: 78%
“…Of these 24 papers, 22 report about the development of one or more risk model or score [24][25][26][27][28][29][30][31][32][33][34][35]37,38,[40][41][42][43][44][45][46][47], and 2 studies report about the development and external validation of one or more risk model or scores on an external population [36,39].Overall, the 24 studies reported 40 models, out of which 24 models were selected for full data extraction. The rest (16 models) were not selected, either because they were judged to be minimally different from the reported ones or they were not the preferred models by the authors or they were significantly deficient in details or statistical reporting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. siMS score y siMS risk score (por sus siglas originales en inglés), el primero de ellos fue propuesto para la evaluación del estatus del SM y el segundo para evaluar el riesgo de enfermedades coronarias o eventos cerebrovasculares. siMS score se calcula a partir del índice CC/T, glicemia, TGL, presión arterial sistólica y HDLc, considerando los puntos de corte empleados para definición de SM en el caso de las cuatro últimas variables nombradas (24) , siMS risk score incorpora la edad y el antecedente familiar de evento cardio o cerebrovascular a los mismos elementos de siMS score (24) . Estos scores se obtuvieron con ayuda de la hoja de cálculo suministrada por Soldatovic et al (24) , y se introdujeron los puntos de corte de la definición de SM que se aplicó en la presente investigación.…”
Section: Personal Debidamente Entrenado Realizó Una Venopunciónunclassified
“…siMS score se calcula a partir del índice CC/T, glicemia, TGL, presión arterial sistólica y HDLc, considerando los puntos de corte empleados para definición de SM en el caso de las cuatro últimas variables nombradas (24) , siMS risk score incorpora la edad y el antecedente familiar de evento cardio o cerebrovascular a los mismos elementos de siMS score (24) . Estos scores se obtuvieron con ayuda de la hoja de cálculo suministrada por Soldatovic et al (24) , y se introdujeron los puntos de corte de la definición de SM que se aplicó en la presente investigación. Ya que por el momento no existen puntos de corte para los puntajes descritos, se calculó el percentil 85 de cada uno.…”
Section: Personal Debidamente Entrenado Realizó Una Venopunciónunclassified